Peningkatan Hasil Belajar Peserta Didik Pada Pembelajaran Las Oksi Asitelin dengan Menggunakan Model Project Based Learning di SMK Negeri 3 Makassar Berbasis Guru Efektif - Fiskia Rera Baharuddin; Nurlaela Latief (Seminar Nasional LP2M UNM, 2019)
This study aims to: a) improve the learning outcomes of acetylene welding oxy learning students in SMK Negeri 3 Makassar; b) get evidence of an increase in the learning outcomes of oxy acetelin welding at SMK Negeri 3 Makassar. This research is a Classroom Action Research (CAR) carried out in 2 cycles. This study uses the Kemmis & Taggart design which includes planning, implementing actions, observing and reflecting activities. Data collection uses observation techniques, field notes, and interviews. Based on the results of the study in each cycle it appears that before the action is carried out the value of 67.61 with a graduation rate of 13.89%, after taking action in the first cycle, the value of students gained by students increases to 70.95 with a graduation rate 60.22%, then the second cycle increased the average value to 84.19 with a passing rate of 100%. To clarify the increase in the assessment of the work that has been carried out. Student learning outcomes after using the Project Based Learning learning model has increased, so that the level of student scores by 100% with a very good category. These results can be concluded that the Project Based Learning learning model can improve the learning outcomes of students in the learning of oxy acetylene welding, it also has an impact on improving the learning achievement of oxy acetylene welding.